2022
DOI: 10.3390/biom12070942
|View full text |Cite
|
Sign up to set email alerts
|

The Detrimental Role of Intraluminal Thrombus Outweighs Protective Advantage in Abdominal Aortic Aneurysm Pathogenesis: The Implications for the Anti-Platelet Therapy

Abstract: Abdominal aortic aneurysm (AAA) is a common cardiovascular disease resulting in morbidity and mortality in older adults due to rupture. Currently, AAA treatment relies entirely on invasive surgical treatments, including open repair and endovascular, which carry risks for small aneurysms (diameter < 55 mm). There is an increasing need for the development of pharmacological intervention for early AAA. Over the last decade, it has been increasingly recognized that intraluminal thrombus (ILT) is involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 135 publications
0
4
0
Order By: Relevance
“…The results of our meta-analysis suggest that antiplatelet agents do not affect AAA process, either in terms of sac expansion, reduction, or rupture. Although some of the findings hold opposite opinions, an increasing number of studies suggest that the effectiveness of antiplatelet agents in slowing the expansion of AAA may be due to the antiplatelet agents’ capacity to decrease platelet-derived cytokines expression and plasminogen activation, and to diminish the infiltration of platelets and macrophages within the vascular wall [ 11 , 13 , 22 , 23 ]. Our findings may be different, as meta-analysis does not demonstrate any significant differences in growth rates in patients taking antiplatelet agents (MD = –0.04, 95% CI = [–0.37, 0.30]) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of our meta-analysis suggest that antiplatelet agents do not affect AAA process, either in terms of sac expansion, reduction, or rupture. Although some of the findings hold opposite opinions, an increasing number of studies suggest that the effectiveness of antiplatelet agents in slowing the expansion of AAA may be due to the antiplatelet agents’ capacity to decrease platelet-derived cytokines expression and plasminogen activation, and to diminish the infiltration of platelets and macrophages within the vascular wall [ 11 , 13 , 22 , 23 ]. Our findings may be different, as meta-analysis does not demonstrate any significant differences in growth rates in patients taking antiplatelet agents (MD = –0.04, 95% CI = [–0.37, 0.30]) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that aspirin and therapeutic anticoagulants were not significantly associated with HO-1 expression ( p 0.05) and were unable to induce HO-1 gene overexpression to provide protection against oxidative stress cells. On the other hand, some researchers suggest that antiplatelet agents may indirectly slow down AAA expansion by inhibiting the progression of intraluminal thrombus (ILT) [ 23 , 27 ]. ILT-induced AAA diameter growth and rupture are the results of a combination of mechanisms, including laminar-to-turbulent flow changes due to altered hemodynamics; anterior wall deposition due to asymmetric spatial distribution of ILT in the AAA capsule [ 23 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An in-depth analysis of these deformational changes may reveal additional factors that play a role in the rupture of the aortic wall. Undoubtedly, one of these factors is the intraluminal thrombus, the influence of which has been repeatedly confirmed [ 16 , 17 ]. While previous observations have noted the influence of the symmetry of the intraluminal thrombus location [ 18 ]and its density [ 19 , 20 ], a mechanical representation of this influence on both aneurysm rupture and the occurrence of thromboembolic complications has not been presented.…”
Section: Introductionmentioning
confidence: 99%